Toward a Regional Energy Future: Opportunities and Challenges for Cross-Border Renewable Power Integration in West Africa - Unegbu, Hyginus Chidiebere Onyekachi; YAWAS, Danjuma (Faculty of Engineering, Universitas Semarang, 2026)
Achieving reliable, affordable, and sustainable electricity access remains a critical challenge for power systems in West Africa. Although the region possesses abundant renewable energy resources, fragmented national planning and limited cross-border transmission interconnections continue to restrict optimal resource utilization. This study investigates the technical, economic, and institutional implications of cross-border renewable power integration within the ECOWAS regional power system. Power system modeling was conducted using the PyPSA platform, representing a 14-bus regional network simulated over a full annual operating cycle with high-resolution demand and generation profiles. Three operational scenarios were assessed: Business-as-Usual, private-led Power Purchase Agreements (PPAs), and Coordinated Regional Integration. System performance was evaluated using system marginal costs, renewable energy penetration, transmission utilization, and reliability indices. The results indicate that the Coordinated Integration scenario significantly outperforms the other scenarios, achieving up to a 36% reduction in average system marginal costs, renewable energy penetration exceeding 60%, and improved grid reliability through enhanced load balancing and reserve-sharing mechanisms. In contrast, the Business-as-Usual and PPA-based scenarios exhibit lower performance due to inefficient transmission utilization and institutional fragmentation. The findings highlight that infrastructure expansion alone is insufficient to ensure optimal regional power system performance. Effective integration requires harmonized operational standards, consistent regulatory frameworks, and strengthened regional institutions. Enhancing the roles of the West African Power Pool (WAPP) and the ECOWAS Centre for Renewable Energy and Energy Efficiency (ECREEE), supported by performance-based regional investment mechanisms, is essential to unlock the full benefits of cross-border energy cooperation. This study provides a technically grounded and policy-relevant framework to accelerate energy transition, improve power system resilience, and foster economic integration across West Africa.